Emotion in therapy from science to practice - Hofmann, Stefan G. (New York The Guilford Press, 2016)
"Grounded in cutting-edge scientific research, this book presents innovative ways to explore and work with emotions in psychotherapy. Preeminent clinician-researcher Stefan G. Hofmann accessibly explains how emotions operate, what influences them, and how they can cause distress. He presents strategies that can significantly improve existing evidence-based treatments and promote positive affect and happiness. Clinicians are guided to help clients with any diagnosis gain emotional awareness and use emotion regulation techniques, mindfulness-based practices, and other effective strategies. "In Practice" sidebars highlight specific clinical issues and offer illustrative case vignettes"--Provided by publisher.
1. The nature of emotions -- 2. Individual differences -- 3. Motivation and emotion -- 4. Self and self-regulation -- 5. Emotion regulation -- 6. Appraisal and reappraisal -- 7. Positive affect and happiness -- 8. Neurobiology of emotions -- Appendix I. Common self-report measures -- Appendix II. Progressive muscle relaxation -- Appendix III. Expressive writing.
Includes bibliographical references and index.
Keywords: Emotions; Emotion-focused therapy